2017
DOI: 10.1007/s12010-016-2387-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Study of Carpobrotus edulis Bioactive Properties and Their Effects on Dugesia sicula (Turbellaria, Tricladida) Regeneration

Abstract: The traditional medicinal properties of Carpobrotus edulis are well recognized, particularly in Tunisia where it is used for wound healing. Thus, in this study, biochemical and molecular properties of its leaves' bioactive aqueous-acetone extract were investigated. The total phenolic content (TPC) of the extract was estimated to be 184 ± 5 mg/100 g of fresh matter (FM). The qualitative and quantitative polyphenolic profile was determined by ultra performance liquid chromatography with diode array detection (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Meddeb and colleagues also reported that the aqueous-acetone extract of C. edulis contains different amounts of phenolics such as gallic acid, chlorogenic acid, catechin, 1,3-dicaffeoylquinic acid, caffeic acid and ferulic acid, which were adjudged to be effective against Gram-positive B. cereus and S. aureus as well as S. epidermidis. However, this extract did not show remarkable antimicrobial effects against Gram-negative E. coli, P. aeruginosa, and S. typhimurium [51].…”
Section: Antibacterial Propertiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Meddeb and colleagues also reported that the aqueous-acetone extract of C. edulis contains different amounts of phenolics such as gallic acid, chlorogenic acid, catechin, 1,3-dicaffeoylquinic acid, caffeic acid and ferulic acid, which were adjudged to be effective against Gram-positive B. cereus and S. aureus as well as S. epidermidis. However, this extract did not show remarkable antimicrobial effects against Gram-negative E. coli, P. aeruginosa, and S. typhimurium [51].…”
Section: Antibacterial Propertiesmentioning
confidence: 78%
“…In a study to investigate the potential of the aqueous-acetone extract of C. edulis in a tissue regeneration study using the flatworm Dugesia sicula as a model, the administration of the phenols from the C. edulis extract in the medium of Dugesia sicula at non-toxic concentrations revealed morphological alterations from the macroscopic analysis done, indicating possible toxicological effects of the polyphenols in the extract [51].…”
Section: Toxicity Studies On Carpobrotus Edulismentioning
confidence: 99%
“…Total polyphenolic content (TPC) was evaluated spectrometrically adopting the Folin–Ciocalteu colorimetric method reported by Meddeb et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…There have been several studies on the biological activity of extracts of this species (Table 1). We can find Anti-Proteus [21] and anti-Klebsiella [22] activities of the MeOH and water extracts of South African species, indicating their potential for blocking the onset of rheumatoid arthritis and preventing the onset of ankylosing spondylitis [21,22]; Inhibition on the growth of phagocytosed multidrug-resistant Mycobacterium tuberculosis and methicillin-resistant Staphylococcus aureus of the MeOH/water extract of a species from Sintra, Portugal, suggesting that this plant may serve as a source of new antimicrobial agents that are effective against problematic drug-resistant intracellular infections [23]; neuroprotective properties of the n-hexane, CH 2 Cl 2 , AcOEt and MeOH extracts of a species from Faro, Portugal, suggesting that the consumption of leaves from C. edulis can contribute for a balanced diet and may add to the improvement of cognitive functions [24]; the effect of the MeOH/water extract of an undisclosed species in inhibiting the MDR efflux pumps, enhancing the killing of phagocytosed S. aureus and promoting immune modulation, indicating that the resistance modifier and immunomodulatory effect of this plant extract can be exploited in the experimental chemotherapy of cancer and bacterial or viral infections [25]; antioxidant, metal chelating and anticholinesterase activities of MeOH extracts of species collected in the Algarve, Portugal, together with their fatty acid profile, indicating that C. edulis is a candidate on novel and alternative therapies for the treatment of neurological disorders associated with low levels of acetylcholine in the brain [26]; antioxidant and antimicrobial activity of the acetone/water extract of a species collected in Monastir, Tunisia emphasizing the beneficial cosmetic and therapeutic use of this plant [27]; antioxidant activity of the n-hexane, acetone, EtOH and water extracts of a species from Eastern Cape, South Africa, that may justify the traditional use of this plant in the management of common diseases in HIV/AIDS patients in Eastern Cape Province [28], and inhibition of protein glycation, antioxidant and antiproliferative activities of the EtOH and EtOH/Water extracts of species collected in Sousse, Tunisia [17]. From this study, and by HPLC analysis with standards, sinapic acid, ferulic acid, luteolin 7-O-glucoside, hyperoside, isoquercitrin, ellagic acid and isorhamnetin 3-O-rutinoside were identified [17].…”
Section: Carpobrotus Edulis Lmentioning
confidence: 99%